The link between rhinitis and rapid-eye-movement sleep breathing disturbances in children with obstructive sleep apnea (2014)
Rhinitis and obstructive sleep apnea (OSA) often coexist during childhood. To delineate this clinical association, we examined OSA severity and polysomnogram (PSG) features in children with rhinitis and OSA. Given that rapid-eye-movement (REM) sleep is characterized by nasal congestion, we hypothesized that children with rhinitis have more REM-related breathing abnormalities. We conducted a retrospective cross-sectional analysis of 145 children with PSG-diagnosed OSA. Outcomes included PSG parameters and obstructive apnea–hypopnea index (OAHI) during REM and non-REM. Linear multivariable models examined the joint effect of rhinitis and OSA parameters with control for potential confounders. Rhinitis was present in 43% of children with OSA (n = 63) but overall OAHI severity was unaffected by the presence of rhinitis. In contrast, OAHI during REM sleep in children with moderate–severe OSA was significantly increased in subjects with rhinitis and OSA (44.1/hr; SE = 6.4) compared with those with OSA alone (28.2/hr; SE = 3.8). Rhinitis is highly prevalent in children with OSA. Although OSA is not more severe in children with rhinitis, they do have a distinct OSA phenotype characterized by more REM-related OSA. Further research is needed to delineate the link between REM-sleep and the physiology of the nose during health and disease.